Fungus-originated glucanase and monooxygenase genes in creeping bent grass (Agrostis stolonifera L.). - Yugo Watanabe (Public Library of Science (PLoS), 2021)
Recent studies have revealed presence of fungus-originated genes in genomes of cool-season grasses, suggesting occurrence of multiple ancestral gene transfer events between the two distant lineages. The current article describes identification of glucanase-like and monooxygenase-like genes from creeping bent grass, as lateral gene transfer candidates. An in silico analysis suggested presence of the glucanase-like gene in Agrostis, Deyeuxia, and Polypogon genera, but not in other species belonging to the clade 1 of the Poeae tribe. Similarly, the monooxygenase-like gene was confined to Agrostis and Deyeuxia genera. A consistent result was obtained from PCR-based screening. The glucanase-like gene was revealed to be ubiquitously expressed in young seedlings of creeping bent grass. Although expression of the monooxygenase-like gene was suggested in plant tissues, the levels were considerably lower than those of the glucanase-like gene. A phylogenetic analysis revealed close relationships of the two genes between the corresponding genes in fungal endophyte species of the Epichloë genus, suggesting that the genes originated from the Epichloë lineage.